Metasurfaces & prospects of computer optics - N.L. Kazanskiy; S.N. Khonina (Компьютерная оптика)
Metasurfaces represent a revolutionary paradigm shift in optics that has opened the era of multifunctional light transformations using ultra-thin elements. In contrast to the traditional approach based on refractive and diffractive optical elements, metasurfaces use complex arrays of subwavelength structures to control the phase, amplitude, and polarization of incident light waves. This revolutionary technology offers many advantages, including the creation of ultra-compact optical systems, providing polarization transformations and sharp focusing beyond the diffraction limit, as well as compensation for optical aberrations in a significantly thinner and lighter format. Metasurfaces have been successfully applied in a variety of applications: from high-quality imaging to augmented reality, spectroscopy, environmental monitoring, and improving technology and medical equipment. Due to their remarkable adaptability and exceptional properties, metasurfaces have enormous potential to break the seemingly insurmountable boundaries of light technology. This review presents main applications of metasurfaces in terms of expanding the capabilities of computer optics, discusses challenges and prospects for development, including based on reconfigurable devices and using artificial intelligence methods.